Parent-perceived barriers to accessing services for their child’s mental health problems - Hansen, Anna Sofie (Child Adolesc Psychiatry Ment Health, 2021)
BACKGROUND: Many children and adolescents with impairing mental health disorders are not in contact with specialized child and adolescent mental health services (CAMHS). In order to close the service gap, it is important to increase our knowledge of barriers to access. The aim of this study was to investigate parent perceived barriers to accessing services for their child’s mental health problems to identify potential areas for improvement of access to CAMHS. METHOD: In this cross-sectional observational study 244 parents of children and adolescents referred to outpatient psychiatric assessment were interviewed using the Children’s services interview regarding barriers to accessing child mental health services across healthcare, educational services and social services. Parent reported barriers were analyzed in relation to the child’s age, referral reason, symptom duration and impairment of the child. RESULTS: The most commonly reported barriers were lack of information about were to seek help (60.3%), the perception that professionals did not listen (59.8%) and professionals refusing to initiate interventions or provide referral to services (53.7%). Lack of knowledge, stigmatization and unavailability of services were common themes across barriers to help-seeking. Long symptom duration and parent rated impairment was associated with increased risk of reporting several barriers to help-seeking. CONCLUSION: Parents seeking help for their child’s mental health encounter numerous barriers that could explain part of the treatment gap and long duration of mental health problems in children prior to referral to CAMHS.